Synthesis, Characterization, Antibacterial, Antifungal and Antituberculous Activities of Some Macrocyclic Coordination Compounds of Zn(II), Cd(II) & Hg(II) - Tunali, Yagmur; Canturk, Zerrin; Benkli, Kadriye (Asian Journal of Chemistry, 2010)
The increasing clinical importance of drug-resistant mycobacterial pathogens has lent additional urgency to microbiological research and new antimycobacterial compound development. For this purpose, in this study, Zn(II), Cd(II) and Hg(II) complexes of a heptadentate N5S2 donor Schiff base ligands including 2,6-bis(2-aminothiophenoxymethyl) pyridine and 2,2'-bipyridine- 6,6'-dicarboxaldehyde were obtained by using the literature methods and evaluated for antituberculosis activity. Antituberculosis activities of the compounds were determined by broth microdilution assay, the microplate alamar blue assay, in BACTEC12B medium and results were screened in vitro, using BACTEC 460 radiometric system against Mycobacterium tuberculosis H37Rv (ATCC 27294) at 6.25 μg/mL and tested compounds showed important inhibition ranging from 84 to 58 %. Antimicrobial activities of these complexes have also been searched. All complexes showed the same activity against Pseudomonas aeruginosa and moderate activities against Proteus vulgaris, but they didn't give significant antibacterial activity against other bacterial strains. On the other hand they showed moderate activities when compared with antifungal agent ketoconazole against Candida albicans and Candida globrata.